Antiangiogenic Effect of Isomalyngamide A Riboside CY01 in Breast Cancer Cells via Inhibition of Migration, Tube Formation and pVEGFR2/pAKT Signals - Shih, Ching-Ying; Chang, Tzu-Ting; Chen, Chia-Ling; Li, Wen-Shan (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: To block the metastatic and angiogenic pathways during the tumor progression arouses considerable pharmacological interests in the development of anticancer drugs. Objective: To develop alternative antiangiogenic and antimetastic agents, we designed and prepared a series of nature inspired isomalyngamide A analogs containing ribose conjugate with 1,2-diaminoethane or 1,3- diaminopropane linkers (1-8). Methods: The target glycosylated isomalyngamide A analogs 1-8 were constructed through condensation of the malonic acids 16-19 and the corresponding aminoethoxyl ribosides 20 and 21, using HBTU/DIPEA as the coupling agent. The cell growth inhibition assay, cell migration assay, transwell invasion assay, adhesion assay, tube formation assay and western blot analysis were used to validate the biological actions of compounds. Results: The most effective compound, isomalyngamide A riboside 1 (CY01), possessing a D-ribose core structure and a 1,3-diaminopropane linker, showed significant suppression of MDA-MB-231 cell migration and inhibited tube formation of Human Umbilical Vascular Endothelial Cells (HUVECs) in a dose-dependent manner. Effect of the latter is comparable to that of sorafenib, an orally active multikinase inhibitor and an inhibitor of angiogenesis. CY01 also showed slight inhibition on collagen type IV- and laminin-mediated cell adhesion. These actions may be regulated through the blockade of the VEGF/VEGFR2 signaling pathway by inhibiting the VEGF induced phosphorylation of p-VEGFR2 and p-AKT. Conclusion: In this effort, we have discovered synthetic and glycosylated marine metabolites which may serve as an alternative antiangiogenic and antimetastic agent during multitherapy.
Keywords: tube formation